Stable isotope analysis as a tool to detect illegal trade in critically endangered cockatoos. (9th June 2021) - Andersson, A. A.; Gibson, L.; Baker, D. M.; Cybulski, J. D.; Wang, S.; Leung, B.; Chu, L. M.; Dingle, C.
Abstract: Legal wildlife trade creates opportunities for the sale of illegally procured animals and their derivatives, since it is difficult to differentiate legal from laundered items. This problem is common across many wildlife trade areas – exotic pets, ornaments, seafood – and involves a variety of taxa. Here, we tested the ability of bulk and compound‐specific stable isotope analysis to help monitor and regulate trade of the yellow‐crested cockatoo Cacatua sulphurea, a critically endangered species threatened by overexploitation for the pet trade. Global trade in wild‐caught yellow‐crested cockatoos was banned in 2002; sale of captive‐bred individuals, however, is still permitted. Our surveys in Hong Kong markets revealed more yellow‐crested cockatoos for sale in 2017–2018 than the total number recorded as legally imported over the previous 13 years, emphasizing the need for a forensic tool to identify the source of the individuals for sale in the markets. Stable isotope analysis was successful at distinguishing between captive and wild cockatoos; we found significant differences between wild and captive cockatoos in both stable carbon ( P < 0.001) and stable nitrogen ( P < 0.001) isotope values. Linear discriminant analysis allocated samples to the correct group with high reliability ( Accuracy = 0.91, Kappa = 0.81), although reliability was lower for some individuals with values on the edge of the distribution. In cases where the bulk isotope analysis was ambiguous, compound‐specific stable isotope analysis, which provides carbon isotope values in specific amino acids, can be applied. We found six amino acids that differed significantly between captive and wild samples, with valine ( P = 0.009) being the most informative. Together, stable and compound‐specific isotope analysis represents an important potential forensic tool to help combat illegal trade of cockatoos and could be expanded to other species threatened by wildlife trade. Abstract : It is difficult to differentiate legal from laundered items in wildlife trade. Our surveys in Hong Kong markets revealed more yellow‐crested cockatoos Cacatua sulphurea for sale in 2017–2018 than the total number recorded as legally imported over the previous 13 years, emphasizing the need for a forensic tool to identify the source of the individuals for sale in the markets. We found that bulk and compound‐specific stable isotope analyses were successful at distinguishing between captive and wild cockatoos, based on differences in diet. Bulk carbon and nitrogen isotope values differed significantly between wild and captive cockatoos, as did carbon isotopes of six amino acids – with valine being the most informative. Together, stable and compound‐specific isotope analyses were successful at separating captive and wild cockatoos and, upon further validation, could become an important forensic tool to help combat illegal wildlife trade.